Evaluating glycerol dialkyl glycerol tetraether (GDGT)-based reconstructions from varved lake sediments during the Holocene - Abrook, Ashley M.; Inglis, Gordon N.; Langdon, Peter G.; Bentley, Mckenzie R.; Brauer, Achim; Bull, Ian; Fallows, Daisy; Lincoln, Paul; Ojala, Antti E. K.; Whelton, Helen l.; Martin-Puertas, Celia (Copernicus Publications, 2026)
Advances in proxy development and proxy reconstructions within the Holocene increasingly reveal climatic complexity. Annually laminated (varved) lacustrine records provide an opportunity to assess this complexity at high temporal resolution. Organic geochemical proxies offer the potential for quantitative palaeoclimate reconstruction, however, their application to different varved lake settings remains limited. Here we explore the use of isoprenoid and branched glycerol dialkyl glycerol tetraethers (GDGTs) preserved in varved sediments as proxies for temperature. We analyse three Holocene-aged annually laminated lacustrine records spanning different climate regions and lake settings across Europe (Diss Mere, UK; Nautajärvi, Finland; Meerfelder Maar, Germany); including intervals at multi-decadal resolution within the mid-Holocene. We show that isoprenoid GDGT distributions in annually laminated sediment sequences are largely derived from methanogenic Euryarchaeota and yield unreliable lake surface temperature reconstructions. Conversely, branched GDGT reconstructions show good coherence with instrumental temperature data in mid- and high-latitude environments. Although we show that lake or catchment-specific processes, including differences in processes linked to varve sedimentation, hypoxia, sediment influx and landscape development, can influence brGDGT distributions in varved lakes, the trends and range of variability of our brGDGT derived Holocene temperature reconstructions broadly agree with regional European Holocene reconstructions. This suggests that temperature exerts a first-order control on the methylation of brGDGTs in varved lake sequences. Combined with precise varve chronologies, these biomarker records can be used to generate highly resolved climate data across the Holocene.